2021
DOI: 10.1155/2021/2376148
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Multiobjective Optimization of Mechanical Properties on Sisal‐Glass Fiber‐Reinforced Hybrid Composites Using Response Surface Methodology and LINGO Analysis

Abstract: The aim of this research work was to develop the optimal mechanical properties, namely, tensile strength, flexural strength, and impact strength of sisal and glass fiber-reinforced polymer hybrid composites. The sisal, in the form of short fiber, is randomly used as reinforcements for composite materials, which is rich in cellulose, economical, and easily available as well as glass fibers have low cost and have good mechanical properties. In addition, epoxy resin and hardener were for the fabrication of compos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 30 publications
(32 reference statements)
0
2
0
Order By: Relevance
“…Physical and chemical processes improve the mechanical properties of natural fibers, which also improve the properties of natural fiber composites. Various recent studies have revealed that these natural fibers have the ability to replace synthetic fibers (i.e., glass and carbon fibers) in applications such as automotive and aerospace [17][18][19][20]. Researchers are highly interested in developing materials that can replace synthetic materials.…”
Section: Introductionmentioning
confidence: 99%
“…Physical and chemical processes improve the mechanical properties of natural fibers, which also improve the properties of natural fiber composites. Various recent studies have revealed that these natural fibers have the ability to replace synthetic fibers (i.e., glass and carbon fibers) in applications such as automotive and aerospace [17][18][19][20]. Researchers are highly interested in developing materials that can replace synthetic materials.…”
Section: Introductionmentioning
confidence: 99%
“…Tis article has been retracted by Hindawi, as publisher, following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of systematic manipulation of the publication and peer-review process.…”
mentioning
confidence: 99%